2018
DOI: 10.1093/cercor/bhy041
|View full text |Cite
|
Sign up to set email alerts
|

Neural Cell Adhesion Molecule 2 (NCAM2)-Induced c-Src-Dependent Propagation of Submembrane Ca2+ Spikes Along Dendrites Inhibits Synapse Maturation

Abstract: The neural cell adhesion molecule 2 (NCAM2) is encoded by a gene on chromosome 21 in humans. NCAM2 accumulates in synapses, but its role in regulation of synapse formation remains poorly understood. We demonstrate that an increase in NCAM2 levels results in increased instability of dendritic protrusions and reduced conversion of protrusions to dendritic spines in mouse cortical neurons. NCAM2 overexpression induces an increase in the frequency of submembrane Ca2+ spikes localized in individual dendritic protru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 76 publications
2
25
0
Order By: Relevance
“…Intriguingly, the thin spines are generally accepted as learning spines due to their greater potential for strengthening [76]. Hence, our results suggest that Ppp2r2b may selectively target immature spine structures and further affect synaptic plasticity in OCD pathogenesis, probably through a mechanism similar to that observed with the OCD risk gene NCAM2 [77], which is also detected in our population stratification and differentiation analysis. We also found that reduced expression of Adamtsl3 in neurons led to an increased density of mushroom spines, which are the most mature form of all spines and referred to as memory spines for their pivotal roles in long-term memory [76,78].…”
Section: Discussionsupporting
confidence: 77%
“…Intriguingly, the thin spines are generally accepted as learning spines due to their greater potential for strengthening [76]. Hence, our results suggest that Ppp2r2b may selectively target immature spine structures and further affect synaptic plasticity in OCD pathogenesis, probably through a mechanism similar to that observed with the OCD risk gene NCAM2 [77], which is also detected in our population stratification and differentiation analysis. We also found that reduced expression of Adamtsl3 in neurons led to an increased density of mushroom spines, which are the most mature form of all spines and referred to as memory spines for their pivotal roles in long-term memory [76,78].…”
Section: Discussionsupporting
confidence: 77%
“…Immunocytochemistry was performed as described previously [ 78 ]. Cells were fixed in 4% paraformaldehyde for 30 min at room temperature, washed 2 × 5 min with PBS, and blocked in 4% NGS, 1% BSA, and 0.4% Triton X-100 for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue was rinsed twice in 70% ethanol, washed 3 × 10 min in TBS-T, and mounted with Vectashield with DAPI (Vector Laboratories, USA). Immunocytochemistry was performed as described previously [78]. Cells were fixed in 4% paraformaldehyde for 30 min at room temperature, washed 2 × 5 min with PBS, and blocked in 4% NGS, 1% BSA, and 0.4% Triton X-100 for 1 h at room temperature.…”
Section: Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, knockdown of these CAMs results in reductions in the number of synapses in cultured neurons (Chih and others 2005; De Wit and others 2009). Finally, aside from their structural function in synapse formation and maintenance, CAMs are also capable of promoting intracellular signaling by interacting with cell surface receptors (Cavallaro and Dejana 2011; Dityatev and others 2004; Kiselyov and others 2003; Niethammer and others 2002), or by organizing signaling complexes at synapses via direct or indirect associations with cytosolic enzymes such as kinases (Dalva and others 2007; Sheng and others 2018; Sytnyk and others 2006).…”
Section: An Overview Of Cams and Ionotropic Receptor Traffickingmentioning
confidence: 99%